Care giver burden among spouse of psychiatric patients attending psychiatry outpatient department of a teaching hospital - Basukala, Sulochana (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Caregiver burden in mental illness is a global issue. Burden is more significant and high among spouse than other caregivers. Spouse face illness-specific burdens of feeling powerlessness, fear, marital stress and partnership and family roles. Methods: A cross-sectional study was conducted in outpatient department of psychiatry in Patan hospital, Patan Academy of Health Sciences, Nepal, from 26th August to 23rd September, 2018. Non-probability purposive sampling technique was used. Data was collected from spouses of psychiatric patients by face-to-face interview using Burden Assessment Schedule (BAS) to assess the caregiver burden of spouses of psychiatric patients. Results: Out of 160 spouses interviewed, 94 (59%) had severe burden, 13 (9%) very severe, and 53 (34%) moderate. Burden was significantly associated with respondents’ relation to patient, educational status, income and diagnosis. The respondent’s age, occupation, duration of caring, and place of residence had no significant association with burden. Conclusions: More than half of the spouses of psychiatric patients had severe care giver burden.